COVERAGE OF TODDLER HEALTHCARE SERVICES AND PNEUMONIA OCCURRENCE IN SURABAYA, INDONESIA: AN ECOLOGICAL STUDY: Cakupan Pelayanan Kesehatan Balita dan Kejadian Pneumonia Balita Di Surabaya, Indonesia: Sebuah Ekologi Studi - Arge Wada, A A Arjun; Astutik, Erni; Siti Shofiya Novita Sari; Khan, Rukhsana (Jurnal Berkala Epidemiologi, 2024)
Background: Pneumonia among toddlers is still considered a serious health problem in Indonesia. It can be seen from the high-level coverage of pneumonia cases spread among toddlers. The continued sustainability of life being the key to healthcare development, access to healthcare services for this early-age group is very important. Purpose: This research aims to find out the coverage correlation between healthcare services on the occurrence of pneumonia among toddlers in the city of Surabaya. Methods: The researchers utilize an ecological study design for all districts in the city of Surabaya within the year 2019,2020, and 2021 with the district as the unit of the analysis. The data was analyzed by using Pearson’s and Spearman’s correlation. QGIS application is also used to map and visualize the extent of pneumonia issues and toddler healthcare coverage. Results: The results of the Pearson and Spearman correlation analysis show that toddler healthcare coverage did not correlate with the occurrence of toddler pneumonia in the city of Surabaya. However, several districts in Surabaya City exhibit disparities between toddler healthcare coverage and toddler pneumonia occurrence rates. Conclusion: In the years 2019-2021, the cases of toddler pneumonia fluctuated, whereas in 2020 the number of cases decreased compared to 2019 and then increased again in 2021. The same trend also occurred in toddler healthcare services coverage.